HISTOMORPHOLOGICAL STUDY ON THE CAROTID SINUS IN RABBIT - SADIK , ALI HAMMODI (The Iraqi Journal of Veterinary Medicine, 2022)
Histomorphological study confirmed that the carotid sinus was characterized by an abrupt thinning of elastic tunica media which was rapidly replaced by the normal muscularity of the media on the distal progression in the internal carotid artery. The carotid sinus was richly supplied with sensory receptors which took the form of menisci and left the sinus as the nerve of Hering.